Representation of patriotic feelings in linguistic consciousness - Armiya, E.; Asanbaeva , S.A.; Shoibekova, G.B. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article addresses the issues of selecting, adapting, and digitizing texts of patriotic content in the formation of linguistic consciousness. In contemporary educational contexts, the development of linguistic consciousness capable of generating oral and written texts and transforming them into meaningful communication between the author and the recipient is of particular relevance. At the primary school level, learners, in accordance with their age-related cognitive abilities, gradually acquire grammatical awareness and begin to master basic functional styles of language, which creates favorable conditions for integrating value-oriented content into language education. Linguistic consciousness is an interdisciplinary concept widely applied in philosophy, psychology, pedagogy, and sociology, as it reflects the interaction between language, thinking, and social experience. In primary education, this concept is especially important in the process of forming civic competencies through exposure to texts of patriotic content. Such texts contribute not only to language development but also to the internalization of cultural values and national identity. The study is based on a linguistic analysis of patriotic texts used in educational practice. Special attention is given to the principles of age-appropriate selection and adaptation of materials, as well as to the possibilities of digitization using modern educational technologies. Digital formats enhance accessibility, engagement, and multimodal perception of patriotic content. The article argues that the formation of linguistic consciousness should begin in early childhood, ensuring a balanced development of language competence, civic awareness, and cultural identity.